Nesting site and nest architecture of wallacea endemic stingless bee species Tetragonula cf. biroi and wallacetrigona incisa of Indonesia - Suhri, Andi Gita Maulidyah Indraswari; Soesilohadi, RC Hidayat; Agus, Ali; Kahono, Sih; Putra, Ramadhani Eka; Raffiudin, Rika; Purnobasuki, Hery (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
Generally, stingless bees have distinct geographical distribution and nesting sites, inhabiting tree cavities, rock crevices, land, anthills, and termite nests. Although they have been identified base on their unique morphological characteristics, their nest architecture could be utilized as a potential species identification tool however, inadequate research has been conducted so far. Belonging to the Wallacea species group, Tetragonula cf. biroi and Wallacetrigona incisa share similar brood cell forms. This study was conducted to measure the nesting areas and nest architecture of T.cf. biroi and W. incisa in the Bone regency, the North Luwu, and the South Sulawesi region. The nesting area data was collected by interviewing the local bee breeders and wild bee hunters of the forest. The research included the measurement of the nest entrance, the structure of the food and brood cells, and other nest parts. Observation and measurements of nest characteristics was carried out on five nest architectural forms of T.cf. biroi and one nest architectural form of W. incisa. Ten colonies were observed in each nest shape. The research finding revealed that T.cf. biroi nested on the tree trunk, roof, stone, and land. On the other hand, the nest entrance of W. incisa was hard and thick in texture and dominated by black color. The brood cell form of T.cf. biroi was found variably in either spiral, semispiral, and irregular shape, surrounded by soft and slight involucrum. The brood cell form of W. incisa was found only in spiral form, with thick and stiff involucrum. In both species, the honey pot was located adjoining the nest entrance. The pollen pot was situated behind or under the honey pot. In both species, the nest architecture is determined by microclimatic factors, composite dammar, colony age, and natural antagonists.